Tensile strength variation of pre-strained aluminium alloy due to annealing - Afdila, Aziz (2007)
The automobile is a self-propelled vehicle that travels on land. There are many different styles of cars. Today, the automotive industry is one of the biggest in the world. Body of car is a major component part in the automotive manufactured. Aluminium-Magnesium (Al-Mg) alloys have very good formability properties and have been used extensively for interior structural components of automotive body-inwhite (BIW). However, at elevated temperatures, high diffusivity of Mg atoms allows easy dislocations rearrangements which lead to reduction of mechanical strength (softening/thermal recovery). Straining during' press forming process also the problem in manufactured body of car. The two factors caused the components made out of Al-Mg alloy sheet to be susceptible to softening during paint bake cycle. During studies, softening behaviour is under the influences of time, temperature and pre-strain. The result of this investigation will be useful information for design and selection stages of Al-Mg sheet alloys because it reveals how much softening actually occurring as function of temperature and pre-straining.